A climatology of low‐level jets in the mid‐latitudes and polar regions of the Northern Hemisphere. (10th June 2015) - Tuononen, M.; Sinclair, V. A.; Vihma, T.
Abstract A wintertime climatology of the occurrence and characteristics of low‐level jets (LLJs) in the Northern Hemisphere mid‐latitudes and polar regions was developed. A LLJ detection algorithm was applied to 11 years of Arctic system reanalysis data. The highest occurrence of LLJs was associated with strong gradients in topography and with the sea‐ice edge. Sea areas fully covered with sea ice also favoured the occurrence of LLJs, however, these areas, including the central Arctic, had fewer LLJs than along the sea‐ice edge. LLJs also occurred frequently in the seldom studied Sea of Okhotsk area.